Soil-air partitioning of semivolatile organic compounds in the Lesser Himalaya region: Influence of soil organic matter, atmospheric transport processes and secondary emissions. (15th December 2021) - Riaz, Rahat; Malik, Riffat Naseem; de Wit, Cynthia A.
Abstract: After decades of imposed regulations about reducing the primary emissions of persistent organic pollutants (POPs), these pollutants are still present in the environment. Soils are important repositories of such persistent semivolatile organic contaminants (SVOCs), and it is assumed that SVOCs sequestered in these reservoirs are being re-mobilized due to anthropogenic influence. In this study, concentrations of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) in soil and air, their fugacities, fluxes and the soil-air partition coeﬃcient (KSA ) were determined for three different land cover types (glacial, remote/mountainous and urban) of the Lesser Himalayan Region (LHR). The concentrations of OCPs, PCBs and PBDEs in soils and air ranged between 0.01 and 2.8, 0.81–4.8, 0.089–0.75 ng g −1 ; 0.2–106, 0.027–182, and 0.011–7.26 pg m −3, respectively. The levels of SVOCs in the soil were correlated with soil organic matter (SOM) indicating that SOM is a substrate for the organic pollutants in soils. The Clausius-Clapeyron plots between ln P and inverse of temperature (1000/T) suggested that long range atmospheric transport was the major input source of PBDEs and higher chlorinated PCBs over the LHR. The uneven and wide distribution of local sources in LHR and up-slope enrichment of SVOCs explained the spatial variability and altitudinal patterns. The soils near mountain and urban lakes act as local sinks of SVOCs such as β-HCH, pp΄ -DDT, CB-28, -118, −153, BDE-47, -99, and −154, with soil-air exchange fluxes tending more toward deposition. However, the soils near glacial lakes acted as local sources of more volatile congeners of α-HCH, γ-HCH, op ′-DDT, pp ′-DDE and lower to medium chlorinated PCBs such as CB-18, -28, −53, −42 and BDE-47, -99, with soil-air exchange tending more toward volatilization flux. Graphical abstract: Image 1 Highlights: Soil organic matter is an important substrate for SVOCs in mountain soils. Glacial soils act as secondary source of SVOCs. Log KSA values showed good agreement for OCPs and lower chlorinated PCBs. In Lesser Himalaya PCBs and PBDEs were mainly received through LRAT. Observed SVOC levels in air were remote lakes > urban lakes > glacial lakes. Abstract : The current study aimed to assess the sources of SVOCs in soil and air of three different environments of LHR. Mountainous and urban environments of LHR may act as potential local sink of organic contaminants, whereas glacial regions of LHR are potential source of SVOCs in the region.